Validation of the SenseWear Armband at high intensity exercise - Drenowatz, C.; Eisenmann, J. C. (European Journal of Applied Physiology, 2011)
The SenseWear Armband (SWA) has been shown to be a valid and practical tool to assess energy expenditure during habitual physical activity. However, previous studies have focused on low-to-moderate intensity activities. The purpose of this study was to assess the validity of the SWA during high intensity exercise. Twenty (ten males, ten females) endurance trained subjects, 24.3 (±2.8) years of age, performed three 10-min treadmill runs at 65, 75, and 85% of their VO2max each and also ran outside for 30 min at their preferred speed. Energy expenditure was measured with the SWA (software version 6.1) and a portable indirect calorimetry system (Jaeger Oxycon Mobile®). The SWA showed a ceiling effect around an intensity of ten METs. Since all subjects exceeded that intensity range during the exercise trials, the SWA significantly underestimated energy expenditure at high intensities. The intra-individual correlations between MET values calculated by the SWA and values derived from the Oxycon, however, were significant for all but two subjects (r = 0.390-0.933, mean = 0.66 ± 0.25). While providing accurate results for energy expenditure during low-to-moderate intensity physical activities, the SWA does not provide accurate estimates of energy expenditure at high intensity levels. The threshold for accurate measurements seems to be around an intensity of ten METs.